Landscape evolution of the granitic Criffel–Dalbeattie hills, south-west Scotland. (2nd October 2021) - Ringrose, Susan; Cassidy, Lin
ABSTRACT: This paper examines the geomorphological evolution of the Criffel–Dalbeattie granitic pluton (CDGP). Research is based on data from Shuttle Radar Topography Mission, Google Earth, Ordnance Survey maps and field measurements. Granitic emplacement into Southern Uplands terrain along Caledonian structural trends took place during the mid-late Devonian. Faulting and subsidence during the late Palaeozoic and Mesozoic preceded assumed differential uplift of the pluton during the early Palaeocene. This led to the development of bidirectional palaeo-surfaces. Structural rather than lithological controls formed the dominant bases for subsequent weathering during the Palaeogene and Neogene. Shallow surface weathering over the CDGP and absence of saprolite imply that weathering episodes may have been relatively short-lived. However, joint enlargement and in situ eroded corestones indicate that earlier weathered features were substantially modified by glacial agencies. Pleistocene glacial events included ice streaming from the NNW which took place over moulded hills. Thinner late-stage ice scoured irregular hill long profiles while divergent ice contributed to basin erosion. Localised resurgent ice streaming was shortlived. After early uplift and palaeo-surface formation, the CDGP hills evolved through phases of granitic weathering and glacial erosion likely over the past 65 Ma since the early Palaeocene.